Protecting the Meghna River a sustainable water resource for Dhaka. - Chowdhury, Farhat Jahan (Metro Manila, Philippines Asian Development Bank, 2019)
The authors assess the threats facing the Meghna River and identify protection measures needed to ensure that it can provide a sustainable and safe supply of drinking water. These measures include designating ecological critical areas, promoting cleaner industrial production, monitoring pollution, controlling wastewater discharges and pesticide use, and empowering local stewardship of the river.
Keywords: Water resources development -- Government policy -- Asia; Water -- Law and legislation -- Asia; Electronic books